Selection of Fish Raw Material Suppliers by Integrating ANP and Topsis Methods in CV. Riki Utama Mandiri - Aula Fajar Iman Sakti; Wiwik Sulistiyowati (Procedia of Engineering and Life Science, 2021)
CV. Riki Utama Mandiri is a company in distributing an economic fish frozen product. This company distributed any kind of retail and wholesaler, both domestic and export. They distributing many frozen fish products variant such as Patin Fillet and Shark Fin. The all raw materials of those frozen seafood was obtained by three different suppliers. The common problems found in CV. Riki Utama Mandiri mostly about raw patin fish supplier which often committed delivery delays. The purpose of this research is to fixing the supply chain management in deciding the more accurate selections of raw materials supplier. To overcome the common problems that happen. Analytical network process (ANP) will simplify the criteria weight values and sub criteria of each supplier. Meanwhile, technique for others reference by similarity to ideal solution (TOPSIS) method is used for giving a rank order of the alternative supplier. This research is expected for being a consideration for the company in obtaining a good and more effective kind of raw supplier. We also expecting the company for tighten supplier selection more effective way so that it can fullfilled the existing standard. Also to overcome the common problems such as delivery delays, competing raw materials with uncertain quality, and difficulty in sort out the raw materials due to size issues.